Interview with the novelist Jose Luis De Juan - De Juan, Jose Luis; Walton, Sarah (The University of Hull)
Recording of an interview with the novelist Jose Luis De Juan, carried out by Sarah Walton on 3rd September 2013, at the novelist's home in Deia, Mallorca.